2018
DOI: 10.1002/jmri.25957
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative susceptibility mapping (QSM) as a means to monitor cerebral hematoma treatment

Abstract: 2 Technical Efficacy: Stage 2 J. Magn. Reson. Imaging 2018;48:907-915.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
9
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 40 publications
1
9
0
Order By: Relevance
“…Moreover, the thrombus susceptibility value showed higher accuracy than the SVS diameter for predicting cardioembolic stroke, indicating that thrombus susceptibility can be used as an imaging biomarker of cardioembolism in acute ischemic stroke. Similar findings have been reported in intracranial hemorrhage studies, in which susceptibility values showed improved accuracy in assessing both hematoma and microbleed burden (17,29). Cardioembolic stroke is easily misdiagnosed in clinical practice.…”
Section: Discussionsupporting
confidence: 82%
“…Moreover, the thrombus susceptibility value showed higher accuracy than the SVS diameter for predicting cardioembolic stroke, indicating that thrombus susceptibility can be used as an imaging biomarker of cardioembolism in acute ischemic stroke. Similar findings have been reported in intracranial hemorrhage studies, in which susceptibility values showed improved accuracy in assessing both hematoma and microbleed burden (17,29). Cardioembolic stroke is easily misdiagnosed in clinical practice.…”
Section: Discussionsupporting
confidence: 82%
“…A previous study showed a strong correlation between magnetic susceptibility and the concentration of gadolinium (10). Susceptibility also correlated well with the concentration of iron in phantoms (11), deep gray matter (7,12,13), and hemorrhage (14,15). However, few studies have examined the relationship between CT attenuation values and susceptibility in intracranial areas that contain paramagnetic materials such as iron and diamagnetic materials such as calcification.…”
mentioning
confidence: 93%
“…The quantification of iron overload provides useful information in defining the therapeutic time window and the optimal duration of these treatments. Although quantitative susceptibility mapping (QSM) is more accurate for iron quantification (18), SWI is a widely available sequence and can be used in the routine clinical evaluation of iron overload after ICH.…”
Section: Discussion/conclusionmentioning
confidence: 99%